Channel shortening in IFDMA-SIMO system - XU Lan; WANG Zong-xin (Tongxin xuebao)
In high-speed IFDMA systems,the increase of channel memory can lead to serious multi-path interference.After a brief introduction to IFDMA system,a new channel shortening algorithm based on the presented IFDMA-SIMO system model was proposed.Simulation results show that the proposed algorithm can effectively suppress multi-path in-terference while maintaining the orthogonality among the signals from different users.